Cross-cultural features of tour groups service from Sri Lanka - N. A. Zamyatina; A. V. Zbarskaya; Yu. O. Tsunaeva (Вестник университета)
An important component of the tourist image of the region is the monitoring of area customer's satisfaction with the level and volume of services provided. There are certain special requirements to anticipate needs of guests from any of the countries, at the same time the most apparent differences concern welcoming guests from Asian countries. The theoretical material of cross-cultural approach to social and business communications has been summarized in the article, the challenges have been revealed and areas for improving quality of tourist services for mass tourism and incentive tour package groups from Sri Lanka have been considered.